(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The estimation of stability of plant communities and ecological strategy of species in the conditions of the anthropogenic transformation of the environment in different agrocenoses of the Crimea is given. In segetal communities, euhemeroby (from 65 % to 98 %) and CRstrategy (43-61 %) predominate. In perrenial agroconoses, the increase of oligo- and mesohemeroby (up to 27 %), species with C-strategy (up to 25 %) and CSR-strategy (up to 27 %) has been observed. The greatest indexes of hemeroby (from -80 up to -90) are typical for cereal plantations and crop cultures.